Diversity and seasonal variation of endophytic fungi associated with bark, stem and leaf of agar plant (Aquilaria malaccensis Lam.) (Journal of Biodiversity Conservation and Bioresource Management, 2023)
The diversity of endophytic fungi was isolated from the bark, stem and leaf of agar plant in  monsoon and winter seasons at different locations of Dhaka and Habiganj districts. A total of 25 fungal isolates were found in monsoon and 22 in winter season. The highest diversity value was found in the bark of location 2 in monsoon according to Shannon diversity index and in the stem of location 1 in winter according to Simpson diversity index. The lowest value was found in the leaf and stem of location 1 and 4, respectively. The evenness of endophytic fungi was highest in the stem of location 1 and lowest in leaf in monsoon based on Shannon evenness index. The maximum species richness was recorded in the bark of location 2 (Margalef’s index) and in the stem of location 1 in monsoon (Menhinick’s index), and the minimum value recorded in the bark of location 4 in monsoon season.Biodivers. Conserv. Bioresour. Manag. 2023, 9(2): 65-74